Workshop Pembuatan Media Ajar Berbasis Android Bagi Mahasiswa Praktek Lapangan Kependidikan (PLK) Kota Padang - Monica Fransisca; Yuliawati Yunus; Renny Permata Saputri (Unri Conference Series: Community Engagement, 2021)
Online lectures at FKIP Universitas Putra Indonesia 'YPTK' causes the preparations for practice teachers were not fulfilled, the same with their ability in making a good learning media. This community service activitywere carried out in a form of utilizing innovation in learning media by practice teachers whose will carry out an online learning (as affected by covid-19 pandemic). The purposes of this activity is to provided training on the design and creatingandroid based learning media. The subjects of this services are practice teachers at Faculty of Teacher Training and Education, Universitas Putra Indonesia 'YPTK' Padang. The method used in this service is a workshops which contains with a steps of preparation, screening, implementation, evaluation and reports. After conducting the workshops, most of the practice teachers were able to understood the courses and created an innovations of android-based leaning media which would be implemented later on to students during online learning. The android based learning media would be a help forpractice teachers to convey their courses. All of the practice teachers were very enthusiastic in this activity, judging from the 90% of satisfaction’saverage, and hopefully they could carry out their teacher training very well and confidently.